Wideband Frequency Selective Surface Based Transmitarray Antenna at X-Band - Muhammad Naeem Iqbal; Mohd Fairus Mohd Yusoff; Mohammad Kamal A Rahim; Mohamad Rijal Hamid; Farid Zubir; Zaharah Johari; Huda Bin A Majid (IAES Indonesian Section, 2020)
In this paper, a wideband multilayer transmitarray antenna is designed for Ku frequency band. The unit cell is designed at 12GHz using frequency selective surface structure. Double square ring with center patch based multilayer unit cell is simulated. The effect of substrate thickness variation on transmission coefficient magnitude and phase range is discussed. The horn antenna designed at X-band will be used as feed source for transmitarray antenna. Transmitarray simulation results show wide impedance bandwidth from 10 to 13GHz. Wide gain bandwidth of 1.975GHz with peak gain of 18.96dB is achieved. The proposed transmitarray design will find applications in high gain, directional, low profile antennas for X-band communication systems.